Avaliação das Sub-Frações dos Carboidratos e das Proteinas, Usando as Metodologias do Cncps e In situ com Bovinos da Raça Nelore. 1. Silagem de Milho - Pereira, JRA; Bose, MLV; Boin, C. (Revista Sociedade Brasileira Zootecnia, 1997)
To validate the use of the Cornell Net Carbohydrate and Protein System (CNCPS) under Brazilian conditions, the chemical composition, the potential and the effective degradabilities of the carbohydrate and protein subfractions, and the solid phase passage rate were determined for corn silage in diets with forage:concentrate ratios of 80:20 (DI) and 60:40 (D2) using Nellore cattle. The chromium mordant technique was used to determine the particulate passage rate of solids. For diet 2, there was a reduction in the potentially degradable dry matter (DM), and however not significant, a reduction in the degradation rates of neutral detergent Fiber (NDF, 49%) and neutral detergent insoluble nitrogen (NDIN, 32%), and an increase in the degradation rare of starch (ST, 25%). The use of lag time increased the effective DM degradation (EDDM) of corn silage in both diets (23% and 53% for D1 and D2, respectively). The concentrate ratios did not influence the particulate passage rate of the diets. The higher values related ro the availability of the protein subfractions may indicate a underestimation by CNCPS, Rnd(or) could be attributed to the Zebu animals used in this study.
Evaluation of the carbohydrate and protein subfractions, using CNCPS and in situ methodologies with nellore cattle .1. Corn silage
Keywords: carbohydrate; degradability; Nellore; protein; corn silage; Zebu